Interaction between Langmuir and Langmuir-Blodgett films of two calix[4]arenes with aqueous copper and lithium ions - Supian, Faridah L (Langmuir : the ACS journal of surfaces and colloids, 2010)
The binding interactions between aqueous copper (Cu(2+)) and lithium (Li(+)) ions and Langmuir monolayers and Langmuir-Blodgett (LB) multilayers have been investigated by studying surface pressure-area (Pi-A) isotherms and surface potential-area (DeltaV-A) behavior in order to find the effective dipole moment, mu(perpendicular), of the calixarene molecules in the uncomplexed and complexed states. The orientation of both calix[4]arenes, namely, 5,11,17,23-tetra-tert-butyl-25,27-diethoxycarbonyl methyleneoxy-26,28-dihydroxycalix[4]arene and 5,17-(9H-fluoren-2-yl)methyleneamino)-11,23-di-tert-butyl-25,27-diethoxycarbonyl methyleneoxy-26,28-dihydroxycalix[4]arene, is such that the plane of the calix ring is parallel with the plane of the water surface regardless of the ion content of the subphase. The Gibbs equation was used to interpret the adsorption of ions with both calix[4]arenes as a function of the concentration. Effective dipole moments have been calculated from surface potential values using the Helmholtz equation. In this work, new LB films have been prepared employing two novel amphiphilic calix[4]arene derivatives bearing different upper rim substituents. Thus, the effect of modifiying the upper rim has been observed. The results have shown that these calixarenes may be useful components of ion sensors